(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
In this paper, anattempt is made to discuss some of the important aspects of human resourcemanagement including its importance in software industry. For this purpose thechapter is divided into three parts. First part deals with human resourcemanagement and its conceptual background, the second part deals with importanceof IT industry and the role of HR in the well-being of the industry. The thirdpart deals with objectives of the study and the methodology adopted in detail.